CONTRIBUTIONS OF SHAYKH ‘ABD AL-MAJID ALZINDANI TO AL-I’JAZ AL-‘ILMI - Ab. Rahman, Tazli Sham (Online Journal of Research in Islamic Studies, 2017)
This article highlights the contribution of Shaykh ʻAbd al-Majid bin Aziz al-Zindani, a notable researcher in the study of al-I’jaz al-ʻIlmi (Islamic Scientific Miracles). Al-Zindani has extensively published written materials in supporting al-I’jaz al-ʻIlmi research works based on al-Quran and al-Sunnah as references, which has been used to defend baseless perceptions and accusations due to conflict between Islam and Science. Al-Zindani summarised the important conditions and methods as guideline to the study of al-I’jaz al-ʻIlmi. He was one of the founders of the International Commission on Scientific Signs in Quran and Sunnah and followed by the establishment of al-Iman University in Yemen, which expanded as the Center of Research and Development of al-I’jaz al-ʻIlmi. The main objective of this paper is to review his important information regarding his expertise, as well as his major contributions in the research of al-I’jaz al-ʻIlmi to the Islamic world.